Odpowiedź :
Podstac iloczynowa funkcji kwadratowej
[tex]y=a(x-x_1)(x-x_2)\\x_1=\frac{-b-\sqrt{\Delta}}{2a}\\\\x_2=\frac{-b+\sqrt{\Delta}}{2a}[/tex]
a)
[tex]f(x)=3x^2-x\\\Delta=(-1)^2-4*3*0\\\Delta=1-0\\\Delta=1\\\sqrt{\Delta}=1\\x_1=\frac{1-1}{6}=\frac{0}{6}=0\\x_2=\frac{1+1}{6}=\frac26=\frac13\\a=3\\y=3(x-0)(x-\frac13)\\y=3x(x-\frac13)[/tex]
b)
[tex]f(x)=3x^2-x-10\\\Delta=(-1)^2-4*3*(-10)\\\Delta=1+120\\\Delta=121\\\sqrt{\Delta}=11\\x_1=\frac{1-11}{6}=\frac{-10}6=-\frac{5}3\\x_2=\frac{1+11}{6}=2\\a=3\\y=3(x+\frac53)(x-2)\\[/tex]
c)
[tex]f(x)=-3x^2-x-10\\\Delta=(-1)^2-4*(-3)*(-10)\\\Delta=-119\\\Delta < 0\\\text{Brak rozwiazan = nie mozna zapisac w postaci iloczynowej}[/tex]
d)
[tex]f(x)=-3x^2+10\\\Delta=0^2-4*(-3)*10\\\Delta=0+120\\\Delta=120\\\sqrt{\Delta}=\sqrt{120} = \sqrt{2*6*2*5}=2\sqrt{30}[/tex]
[tex]x_1=\frac{-2\sqrt{30}}{-6}=\frac13\sqrt{30}\\x_2=\frac{2\sqrt{30}}{-6}= -\frac13\sqrt{30}\\a=-3\\y=-3(x-\frac13\sqrt{30})(x+\frac13\sqrt{30})[/tex]